Technocratic rationality as a legitimizing ideology in a changing plural society : a study in the assumptions, functions and implications of commissions of inquiry with specific reference to the Wiehahn, Riekert and De Lange Commissions - Brown, Dirk Steven Glenn (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1985.